9+8q=11+7q

Simple and best practice solution for 9+8q=11+7q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+8q=11+7q equation:


Simplifying
9 + 8q = 11 + 7q

Solving
9 + 8q = 11 + 7q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-7q' to each side of the equation.
9 + 8q + -7q = 11 + 7q + -7q

Combine like terms: 8q + -7q = 1q
9 + 1q = 11 + 7q + -7q

Combine like terms: 7q + -7q = 0
9 + 1q = 11 + 0
9 + 1q = 11

Add '-9' to each side of the equation.
9 + -9 + 1q = 11 + -9

Combine like terms: 9 + -9 = 0
0 + 1q = 11 + -9
1q = 11 + -9

Combine like terms: 11 + -9 = 2
1q = 2

Divide each side by '1'.
q = 2

Simplifying
q = 2

See similar equations:

| 4(6t+2)=50 | | 4(6t+2)=40 | | 4(6t+2)=28 | | -22(a+6)=-22 | | -3x-2=25 | | 5d-32=8 | | 4r-(-11)=87 | | x/3+4=-2 | | x^4-5x^2-36= | | 10+2(2x-3)=17-(3x-8) | | 3y+78= | | (2x+9)(x+8)=0 | | 8d-22=52 | | 2s+4.6=3s-1.2 | | 5x-32=43 | | 3(m+10)= | | 7x^2=73 | | -5600+200x=0 | | -7(z+4)+3z= | | g-0+4g+6=12 | | 2x*1=x+4 | | -x^2+18x-65=0 | | x/6+7=18 | | r-4/5=-21/4 | | x^3-14x^2y+24xy^2= | | -7(2+4)+32= | | 3(n+2)+15n=114 | | 7x=7(x-2) | | 6x-8=70 | | 6x=2(5x+12) | | 0.75x=-15 | | 9a-3(a-6)=66 |

Equations solver categories